TREN DAN ARAH PENDIDIKAN PERUBAHAN IKLIM DAN PEMBELAJARAN IPA: TINJAUAN LITERATUR SISTEMATIS - Juwita Cristina Situmeang; Helen Veronita Hutapea; Imelda Situmorang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to analyze research trends and directions in climate change education within science learning through a Systematic Literature Review (SLR) approach. Climate change has become a critical global issue that requires not only technological solutions but also educational interventions to improve students’ scientific literacy and environmental awareness. This study adopted the PRISMA 2020 framework, consisting of identification, screening, eligibility, and inclusion stages. A total of 500 articles were initially identified from Google Scholar and ResearchGate using Publish or Perish, with keywords “Climate Change Education” and “Science Learning” (2015–2025). After a rigorous selection process, 12 articles met the inclusion criteria, and 6 articles were analyzed in depth. The data were analyzed using bibliometric analysis with VOSviewer, synthesis matrix, and Critical Journal Review (CJR). The findings indicate that research trends are dominated by themes such as climate education and student engagement, scientific literacy and sustainability, inquiry-based learning, family involvement, and climate impact studies. Furthermore, the results reveal that integrating climate change topics into science learning enhances students’ critical thinking skills, environmental awareness, and engagement in real-world problem solving. However, research gaps remain, particularly in the integration of climate change education into formal curricula, experimental studies, and research in developing countries. This study provides important insights for educators, researchers, and policymakers in developing more effective and contextual science learning related to climate change.